Managing Excess Lead Iodide with Functionalized Oxo-Graphene Nanosheets for Stable Perovskite Solar Cells - Li, G.; Li, M.; Agyei-Tuffour, B.; et al. (Angewandte Chemie International Edition, 2023)
Stability issues could prevent lead halide perovskite solar cells (PSCs) from commercialization despite it having a comparable power conversion efficiency (PCE) to silicon solar cells. Overcoming drawbacks affecting their long-term stability is gaining incremental importance. Excess lead iodide (PbI2) causes perovskite degradation, although it aids in crystal growth and defect passivation. Herein, we synthesized functionalized oxo-graphene nanosheets (Dec-oxoG NSs) to effectively manage the excess PbI2. Dec-oxoG NSs provide anchoring sites to bind the excess PbI2 and passivate perovskite grain boundaries, thereby reducing charge recombination loss and significantly boosting the extraction of free electrons. The inclusion of Dec-oxoG NSs leads to a PCE of 23.7% in inverted (p-i-n) PSCs. The devices retain 93.8% of their initial efficiency after 1,000 hours of tracking at maximum power points under continuous one-sun illumination and exhibit high stability under thermal and ambient conditions. [*] Dr. G. Li,+ Prof. Dr. M. Li, Y. Tang, Z. Zhang Key Lab for Special Functional Materials of Ministry of Education, National & Local Joint Engineering Research Center for High efficiency Display and Lighting Technology, School of Materials Science and Engineering, Collaborative Innovation Center of Nano Functional Materials and Applications, Henan University Kaifeng 475004 (China) E-mail: mengli@henu.edu.cn Dr. G. Li,+ Prof. Dr. M. Li, Dr. A. Musiienko, F. Akhundova, J. Li, K. Prashanthan, Dr. F. Yang, S. Trofimov, S. Zuo, L. Wu, L. Wang, Dr. Y. Yang, Dr. B. Agyei-Tuffour, Dr. R. W. MacQueen, Dr. B. Naydenov, Dr. T. Unold, Prof. Dr. E. Unger, Prof. Dr. A. Abate Helmholtz-Zentrum Berlin für Materialien und Energie GmbH Hahn-Meitner-Platz 1, 14109 Berlin (Germany) E-mail: antonio.abate@helmholtz-berlin.de Dr. G. Li,+ Prof. Dr. A. Abate Department of Chemistry, Bielefeld University Universitätsstraße 25, 33615 Bielefeld (Germany) Dr. G. Li+ Present address: Institute of Chemical Sciences and Engineering, École Polytechnique Fédérale de Lausanne (EPFL) 1015 Lausanne (Switzerland) Dr. Y. Hu,+ Q. Cao, Prof. Dr. S. Eigler Institute of Chemistry and Biochemistry, Freie Universität Berlin Altensteinstraße 23a, 14195 Berlin (Germany) E-mail: siegfried.eigler@fu-berlin.de Dr. Y. Hu+ CNRS, Immunology, Immunopathology and Therapeutic Chemistry, UPR3572, University of Strasbourg, ISIS 67000 Strasbourg (France) K. Prashanthan Department of Physics, University of Jaffn
Research Article
Keywords: solar cells; perovskite; iodide (PbI2); nanosheets